Experimental Study on Residual and Dissolution of DNAPL in Transparent Fracture. (11th January 2023) - Wu, Junyu; Zhu, Shu; Zhu, Zhende; Lu, Bin; Wang, Luxiang
Abstract : Dense nonaqueous phase liquid (DNAPL) is one of the main pollution sources of the underground environment. After DNAPL enters the underground environment, the migration and diffusion process has experienced a variety of media, resulting in large-scale and long-term pollution. To better understand the residual and dissolution process of DNAPL in fractures, the visual experiment of DNAPL residual and dissolution in the fracture was carried out using the transparent fracture model made of glass material, and the changes of DNAPL migration morphology and residual distribution in the crack were obtained. The results showed that the migration front of DNAPL in the fracture was finger shaped in the process of displacement of water phase by DNAPL phase, which was consistent with the state in porous media. When the process of water phase displacing DNAPL phase was over, discrete and aggregated DNAPL droplets remained in the fracture. The residual DNAPL was mainly concentrated in the area ranged from 0.3 mm to 0.8 mm. The dissolution rate of DNAPL in the fracture changed from fast to slow, and there was an obvious tailing period. The increased velocity of water phase flow significantly shortened the time of dissolution process. The DNAPL with hydrolysis reaction accounted for only 0.86% on average in the dissolution process. The findings of this study are helpful to the remediation of the underground environment.